The relationship of household income and health expenditures the case of the Philippines - Jimenez, Laurelle Amary N.; Jose, Carlos Miguel D.
This study investigated the relationship between household income and health expenditures in the Philippines. Specifically, it aimed to (1) determine whether higher household income would lead to increased health expenditures, (2) identify socioeconomic and demographic factors that characterize health expenditure patterns across different income levels, and (3) investigate the effects of COVID-19 on the health expenditure patterns before and after the pandemic. The study used the Capability Approach and Human Development Index as theoretical frameworks to understand how increased income affects households' ability to access healthcare services. Data were sourced from he Family Income and Expenditure Survey (FIES) of the Philippine Statistics Authority (PSA), utilizing 141,569 and 159,370 samples for 2018 and 2023, respectively. The study found that household income, during pre- and post post-pandemic, has a positive relationship with health expenditure. Additionally, households in the agricultural sector, and those that receive remittances, those that lease non-agricultural capital and those that have pensions, allocate more resources to health. The study concludes that income disparities influence health expenditure, highlighting the need to address healthcare inequalities between different income groups. The study recommends reforms in healthcare policies, such as giving priority to low-income households, income-tiered premium subsidies from Philhealth, and improved funding for public hospitals, particularly in rural areas.